2014
DOI: 10.5194/hess-18-2503-2014
|View full text |Cite
|
Sign up to set email alerts
|

Kalman filters for assimilating near-surface observations into the Richards equation – Part 1: Retrieving state profiles with linear and nonlinear numerical schemes

Abstract: Abstract. This paper examines the potential of different algorithms, based on the Kalman filtering approach, for assimilating near-surface observations into a one-dimensional Richards equation governing soil water flow in soil. Our specific objectives are: (i) to compare the efficiency of different Kalman filter algorithms in retrieving matric pressure head profiles when they are implemented with different numerical schemes of the Richards equation; (ii) to evaluate the performance of these algorithms when non… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Subsequently, time series of synthetic "true" matric head and soil moisture profiles are generated for 150 days, by setting the initial profile matric head uniformly equal to −50 cm, and by employing the nonlinear numerical scheme illustrated by Chirico et al (2014). Figure 1 also shows the time series of the generated matric pressure head values at 5 cm depth.…”
Section: Model Implementation and Synthetic Data Generationmentioning
confidence: 99%
See 4 more Smart Citations
“…Subsequently, time series of synthetic "true" matric head and soil moisture profiles are generated for 150 days, by setting the initial profile matric head uniformly equal to −50 cm, and by employing the nonlinear numerical scheme illustrated by Chirico et al (2014). Figure 1 also shows the time series of the generated matric pressure head values at 5 cm depth.…”
Section: Model Implementation and Synthetic Data Generationmentioning
confidence: 99%
“…A common assumption, also adopted in this work, is to set λ = 0.5 and pose m = 1 − 1/n. Chirico et al (2014) showed that the implementation of the filtering approach upon a linearized Crank-Nicolson finite difference scheme (CN) can be an efficient algorithm for onedimensional problems. The differentiation of Eq.…”
Section: Governing Equationmentioning
confidence: 99%
See 3 more Smart Citations